Ideologi dan hegemoni kekuasaan dalam novel Hujan Karya Tere Liye - Sabrina, Silvany Haifa; Nurholis, Nurholis (Aksara: Jurnal Bahasa dan Sastra, 2024)
This research aims to analyze the ideology and power hegemony contained in the novel "Hujan" by Tere Liye. The research method uses qualitative method with content analysis technique. The data obtained from the novel "Hujan" focuses on quotations that describe ideology and power relations between characters. The results showed the representation of authoritarism, capitalism, and socialism in the novel represented through the behavior of characters, such as Lail, Maryam, state leaders, and scientists. In addition, this research also reveals the existence of power hegemony in the novel "Hujan". The power hegemony is depicted by state leaders who create and maintain their dominance through decision-making that affects society. The interaction between civil society and political society is reflected in the relationship between characters and institutions in the story. Thus, this study provides insight into the ideology and hegemony of power in the novel "Hujan" by Tere Liye. The results of this study are expected to help people to understand more about the social dynamics in society as well as the role of literature in reflecting and strengthening the ideology held by the dominant group.Keywords: Novel Hujan, Ideology, Hegemony